THE INTERRELATION OF EUCHARIST AND MARRIAGE. THE MISSION OF THE PARISH IN FORMING COMMUNICANTS AND SPOUSES IN HOLINESS - LEMASTERS, Philip (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2016)
Orthodox parishes today must enable communicants and spouses to recognize how their communion with Jesus Christ calls them to a holy communion with one another. Eucharist and marriage both manifest a covenantal communion that changes the identity of the persons who participate in them from isolated individuals to participants in the Body of Christ. They also involve physical actions that transcend the merely physical in their significance, and thus resist the Gnostic tendencies of separating body and person” They both draw on the deep incarnational sensibilities of Orthodoxy. Sacrifice is central to both sacraments, as husband and wife wear the crowns of martyrdom as they offer themselves to one another and to the Lord, in whose offering they commune in the Eucharist.